Rotatividade de pessoal no serviço público: um estudo das universidades federais do nordeste brasileiro - Pereira, Elainy Danielle Guedes (Universidade Federal Rural do Semi-Árido, 2018)
This study aims to conduct an empirical examination of the main aspects of personnel turnover in federal universities in the Brazilian Northeast, reflecting the possible reasons for this. In this way, the work is initially developed through bibliographical research, seeking to explore the main theoretical contributions on the subject and, later, through research with the federal universities of the Northeast of Brazil. After establishing the variables and collecting data, the relationships between the dependent variables (turnover index, number of provisions and number of vacancies) and independent variables (institutional and municipal variables) were established using a multiple regression to indicate how the independent variables affect the turnover rate of the Organs studied. The provisions in the Federal Public Administration are, for the most part, stable and with lasting ties. However, despite the relative remuneration patterns and the different working conditions, public servants have abandoned their positions in search of other Careers or institutions. Therefore, recognizing the possible causes and motivations for the exit of these servers can promote a revision in the processes and policies of management of the Institutions, in order to identify and develop strategies to combat the turnover and organizational costs arising from them. Based on the data obtained, it is possible that only one institution, of which the sample is composed, periodically monitors the turnover rates of effective personnel and that none reported having strategies to combat this occurrence. With the analysis of the data, it is recognized that the main form of entry of effective servers, in the considered period, is the Appointment. In relation to the main movement of voluntary termination, in the year 2017, we have Vacancy for possession in another position unaccountable. Given the above, it is observed that in the majority of occurrences in the period, whether of entry or exit of servers, it is observed the superiority of the movements occurred between the technical-administrative servers. Seeking to identify which variables positively or negatively impacted on the voluntary dismissal of federal public universities' servers in the Northeast, it can be seen that most of the municipal variables negatively influence the Rotativity Index. In the number of appointments and exits, the influence of the distance between the municipality and the capital of the Federation Unit stands out. Thus, the results can show the relation of the expectations of the server when the option for an institution, observing its municipal location. Therefore, the choice of joining or leaving a particular campus of an institution may be related to personal expectations regarding the possibility of the municipality being able to offer social and economic well-being to the server and its relatives, showing that staff turnover may be more related to personal and family interests than to a probable professional projection. Therefore, despite the importance of identifying the factors influencing turnover and considering the relevance and main effects of this in the organizational process, it is possible to verify the lack of studies and management policies inherent to turnover in the management of people in the public sector. This lack of organizational studies and strategies is therefore a critical issue
Keywords: Gestão de Pessoas; Rotatividade de Pessoal; Teoria das Expectativas; Administração Pública; People Management; Turnover; Theory of Expectations; Public Administration; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA